2018
DOI: 10.1002/aocs.12149
|View full text |Cite
|
Sign up to set email alerts
|

Combined Esterification and Short‐Path Distillation for High‐Purity Pentaerythritol Ester from Palm Kernel for Biolubricants

Abstract: The development of specialty esters using palm-based materials through a solventless and autocatalytic method was investigated. The C 8− C 10 fatty-acid esters of pentaerythritol are the bases for high-performance lubricants. In the present study, an easy and efficient method was developed using an esterification process coupled with short-path distillation to produce high-purity pentaerythritol ester (PEE) for the more complete removal of acid value (AV) in the end products. The compositions of the distilled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…This process can aid the palm oil mills in meeting the regulation limits set by the Department of Environment. POME was also evaluated as a carbon source for microalgae growth (Idris et al, 2018). The benefit from doing this is that the POME gets treated and the cost of algae cultivation is reduced.…”
Section: Innovations In the Milling Sectormentioning
confidence: 99%
See 2 more Smart Citations
“…This process can aid the palm oil mills in meeting the regulation limits set by the Department of Environment. POME was also evaluated as a carbon source for microalgae growth (Idris et al, 2018). The benefit from doing this is that the POME gets treated and the cost of algae cultivation is reduced.…”
Section: Innovations In the Milling Sectormentioning
confidence: 99%
“…The study showed that cultivation of algae in POME has managed to reduce the PO 4 , NO 3 , NO 2 and the COD in POME. Based on the fatty acid profile, the POME cultivated microalgae also showed good potential to be used as biodiesel (Idris et al, 2018).…”
Section: Innovations In the Milling Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, Fourier‐transform infrared spectroscopy (FTIR) and nuclear magnetic resonance (NMR) spectroscopy are convenient techniques used to make a quick analysis of pentaerythritol esters . However, these two methods only provide functional group information, and the composition of mixed esters could not be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, Fourier-transform infrared spectroscopy (FTIR) and nuclear magnetic resonance (NMR) spectroscopy are convenient techniques used to make a quick analysis of pentaerythritol esters. 4,5 However, these two methods only provide functional group information, and the composition of mixed esters could not be determined. To characterize the ingredients of pentaerythritol esters, separation, and qualitative and quantitative analysis using chromatography and mass spectrometry (MS) are required.…”
mentioning
confidence: 99%